ANALISIS FAKTOR PENENTU PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERBANKAN SYARIAH DI INDONESIA - Usamah Usamah; Tutut Dwi Andayani (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
This study aims to determine the effect of the size of the bank on the disclosure of Islamic Social Reporting (ISR) on Islamic banks, as measured by the Islamic Social Reporting (ISR) indeks. The population of this research is all sharia banks that exist in Indonesia. The total sample were tested as many as nine Islamic banks period 2013 – 2016 with purposive sampling method. This research analyzes ISR through annual bank report using content analysis method. The analytical method is using multiple linear regression, before regresed done classical assumption test is the first. The results of this study indicate that from year to year disclosure ISR has increased. Simultanly commisssioners board size variable, frequency of the audit committee meetings, , liquidity, leverage, profitability and the bank size significantly on Islamic Social Reporting (ISR) disclosur. Partially only the bank size variable that significant effect to the Islamic Social Reporting (ISR) diclousure. While for commisssioners board size variable, frequency of the audit committeemeetings, sharia supervisory board size, frequency of the sharia supervisory board meetings, liquidity, leverage, profitability doesn’t have significant effect to the Islamic Social Reporting (ISR) diclousure